Upper limits for absorption by water vapor in the near-UV. (February 2016) - Wilson, Eoin M.; Wenger, John C.; Venables, Dean S.
Abstract: There are few experimental measurements of absorption by water vapor in the near-UV. Here we report the results of spectral measurements of water vapor absorption at ambient temperature and pressure from 325 nm to 420 nm, covering most tropospherically relevant short wavelengths. Spectra were recorded using a broadband optical cavity in the chemically controlled environment of an atmospheric simulation chamber. No absorption attributable to the water monomer (or the dimer) was observed at the 0.5 nm resolution of our system. Our results are consistent with calculated spectra and recent DOAS field observations, but contradict a report of significant water absorption in the near-UV. Based on the detection limit of our instrument, we report upper limits for the water absorption cross section of less than 5×10 −26 cm 2 molecule −1 at our instrument resolution. For a typical, indicative slant column density of 4×10 23 cm 2, we calculate a maximum optical depth of 0.02 arising from absorption of water vapor in the atmosphere at wavelengths between 340 nm and 420 nm, with slightly higher maximum optical depths below 340 nm. The results of this work, together with recent atmospheric observations and computational results, suggest that water vapor absorption across most of the near-UV is small compared to visible and infrared wavelengths. Highlights: The absorption cross section of water vapor was studied from 325 to 420 nm. The upper limit was 5×10 −26 cm 2 molecule −1 above 340 nm at 0.5 nm resolution. Our result contradicts a recent report of appreciable absorption by water vapor.